Carbon–Sulfur Coupling Reactions Catalyzed by Pd–NHC Complex - Shi, Yanhui; Cai, Zhengyuan; Guan, Pei; Pang, Guangsheng (Synlett, 2011)
I, as the corresponding author, retract the publication by Yanhui Shi et al. “Carbon–Sulfur Coupling Reactions Catalyzed by Pd–NHC Complex” that appeared in Synlett2011, 2090–2096.The intellectual content and factual execution of this work is based on studies carried out in the group of Professor Michael G. Organ at York University, Toronto, Canada during a period prior to 2009, when I was his postdoctoral associate. It was submitted without his prior knowledge and consent. I sincerely regret this serious error in judgment.Professor Yanhui Shi, School of Chemistry and Chemical Engineering, Jiangsu Normal University, Xuzhou, Jiangsu 221116, P. R. of China